(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Maternal health voucher scheme, providing financial support to poor women, is popularly known as subsidies in maternity care services including antenatal, delivery and postnatal care and also economic barriers while seeking treatment from qualified service providers. The aim of this study is to evaluate the association of voucher scheme on receiving maternal healthcare services among the rural women in Bangladesh. Methods: This is a cross sectional study where total sample size was (n=500) rural women who were selected by using convenience sampling method. Among them, 250 women were voucher scheme receivers and other 250 women were non-voucher scheme receivers. A structured questionnaire was adopted for data collection between November and December 2015. In the final analysis, cross tabular analysis and logistic regression model were used, and adjusted odds ratios (ORs) were reported. Results: The study found a strong relation between voucher scheme and maternal healthcare services among the rural women in Bangladesh where majority (88.4%) voucher scheme receivers received information or treatment of Reproductive Tract Infections (RTIs) and Sexually Transmitted Infections (STIs) while non-voucher scheme receivers received only 10%. Most of the respondents (93%) voucher scheme receivers received at least 3 times of antenatal care visit; but only 28% received non-voucher scheme receivers at least 3 times of antenatal care visit. Voucher scheme receivers received 17.127 times more likelihood to receive skilled birth attendance and 25.344 times more likelihood to receive institutional delivery services and positively significant (5 percent) compared to those who did not receive maternal heath voucher scheme. Moreover, 92.4% voucher receivers received transport cost and 73.2%, received safe home delivery services while 22.8% non-voucher scheme receivers received transport cost and only 20.4% received safe home delivery services. Majority (94%) voucher scheme receivers received long time birth control services while only 19.2% non-voucher scheme receivers received long time birth control services. Conclusion: Women who did not receive maternal health voucher scheme found the status of lower antenatal, delivery and postnatal care services receiving trends compared to the women who received the maternal health voucher scheme. It is recommended an effective monitoring system and necessary interventions getting overall developed health status in Bangladesh. Bangladesh Journal of Medical Science Vol.17(4) 2018 p.545-555